Impact of Venture Capital on Innovation and Creation of New Business in Kathmandu Valley - Shrestha, Manjil (Nepalese Journal of Business, 2024)
Abstract This study examines the impact of venture capital on innovation and creation of new business in Kathmandu Valley. Innovation is the dependent variable. The independent variables are government policy, venture capital funding, industry focus of VC firms, market condition, and founder. The primary source of data is used to assess the opinions of the respondents regarding government policy, venture capital funding, industry focus of VC firms, market condition, and founder. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of impact of venture capital on innovation and creation of new business in Kathmandu Valley. The result showed that government policy has a positive impact on innovation. It indicates that supportive government policy regarding venture capital leads to increase in innovation. Similarly, venture capital funding has a positive impact on innovation. It indicate that taking venture capital funding increase in innovation. Likewise, industry focus of VC firms has a positive impact on innovation. It indicates that industry focus of VC firms leads to more innovation in the industry. Further, market condition has a positive impact on innovation. It indicates that favourable market condition leads to increase in innovation. In addition, founder has a positive impact on innovation. It indicates that investing in capable founder leads to increase in innovation.